Synthesis and characterization of Cu+/ MIL-100(Fe) with enhanced catalytic performance for NH3-SCR. (2nd January 2018) - Yong, Shi; Xiao-yu, Sun; Wang, Zhang; Chun-yan, Li; Qidong, Zhao; Jinsuo, Gao; Xinyong, Li
ABSTRACT: A mesoporous MIL-100 (Fe) loaded with Cu + species was synthesized using a hydrothermal method and its denitrification (deNOx) capability for NH3 -SCR process was investigated. From X-Ray diffraction (XRD), hydrogen temperature programmed reduction (H2 -TPR) and X-ray photoelectron spectroscopy (XPS) results, it was concluded that the Cu + has been successfully introduced into the framework structure. Moreover, it was found that copper species play a significant role to promote NO reduction activity of Cu + / MIL-100(Fe) and NO conversion increased with copper amount. Compared with MIL-100(Fe), Cu + /MIL-100(Fe) achieves a 16% increase in the maximum catalytic efficiency at 300°C, suggesting a favorable interaction between metallic copper and iron active sites.